PEWARISAN BEDEKER DI TALANG RIMBO LAMA KECAMATAN CURUP TENGAH KABUPATEN REJANG LEBONG - Warda Wani Purnama Aji; Esy Maestro; Yensharti Yensharti (FBS Universitas Negeri Padang, 2013)
Abstract Bedeker was one of the arts possessed by society at Talang Rimbo Lama Kecamatan Curup Tengah Kabupaten Rejang Lebong which was Islamic. The presentation was a kind of combination between music and dance played in an ensamble. The lyric of the music was derived from words in Al-qur’an accompanied with Rebana and Gendang and the dance was done to beautify the performance. The inheritance of Bedeker was given to the society informally by inheriting to the family and to the environment. The next inheritance step was done by teaching it phase by phase, started from teaching its vocal, then teaching the instruments, and thirds teaching the dance. Kata kunci: Bedeker, Pewarisan, Informal, Rebana, Gendang